Immunoreaction in Chronic Purulent Sinusitis in Girls of Puberty - A, Rasulova N.; H.N., Abdullaev; K.M, Salomov; M.M, Yakubov (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the problem of immune-correction in chronic purulent sinusitis in girls of puberty. The article analyzes the clinical picture of chronic inflammatory diseases of the paranasal sinuses using puberty girls as an example.